Recovery Gonad Betina dan Kontrol Produksi Sperma Secara Hormonal pada Ikan Heterobranchus longifilis - Subagja, Jojo; Gustiano, Rudhy (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
Two experiments were conducted in the IRD-Gamet Laboratory, Montpellier, France. The first experiment was to evaluate the recovery of Heterobranchus longifilis females' gonad after induced ovulation, under tropical condition. Eggs diameter was used as indicator of the recovery rate following by induced breeding, hatching rate and abnormality of larvae. The results showed that the recovery was about 28 - 35 days after ovulation. The second experiment was carried out to improve milt production by hormone treatments, volume of intra testicular sperm and the numbers of spermatozoa were observed. The results indicated that the treatmens did not prove any significant differences. Keywords: hormone, gonad, reproduction, Heterobranchus longifilis ABSTRAK Dua kegiatan penelitian dilakukan di Laboratorium IRD-Gamet, Montpellier, Perancis. Penelitian pertama dilakukan untuk mengetahui recovery gonad ikan Heterobranchus longifilis betina setelah ovulasi, di daerah tropis. Diameter telur digunakan sebagai indikator recovery gonad, diukur pada saat sekitar 28-35 hari setelah ovulasi. Penelitian kedua dilakukan untuk meningkatkan produksi sperma dengan memberikan perlakuan hormon. Volume semen dan jumlah spermatozoa dievaluasi. Hasil penelitian menunjukkan perlakuan tidak memberikan hasil yang signifikan. Kata kunci: hormon, gonad, reproduksi, Heterobranchus longifilis